An improved mathematical model of photovoltaic cells based on datasheet information. (15th March 2020) - Shinong, Wang; Qianlong, Mao; Jie, Xu; Yuan, Ge; Shilin, Liu
Highlights: For PV cells modeling, a two-step modeling method is proposed. PV cells model is separated as ideal model part and resistance network part. For the proposed model, only datasheet information of PV cells is needed. Data in datasheet information is fully utilized in the processing of modeling. Abstract: In order to tackle the nonlinear transcendental equation and intractability of traditional photovoltaic (PV) cells model, this paper proposes a two-step modeling method based on datasheet information. Firstly, grounded on the assumption that the open circuit voltage and short circuit current are independent of series resistance R s and shunt resistance R sh, the PV cells model is separated as the ideal model part and the resistance network part. Then, according to the data provided by the manufacturer under Standard Test Conditions (STC) and Nominal Operating Cell Temperature (NOCT) conditions, the parameters photocurrent I ph, reverse saturation current I o and ideality factor n are obtained to achieve the purpose of modeling the ideal model part. Meanwhile, the parameters R s and R sh are obtained according to the data provided by the manufacturer under STC to achieve the purpose of modeling the resistance network part. Finally, the open circuit voltage and short circuit current of three different material types of PV cells are obtained by the modeling method and compared with the actual experimental data to verify the mentioned assumption. Moreover, the current-voltage characteristic curves of these three PV cells are also obtained and the corresponding errors are analyzed and discussed.